History of the Mts Al-Inthisor Educational Institution Bendega Tanjung Karang Sekarbela Mataram City, West Nusa Tenggara - Mauzifa Mauzifa (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2024)
This article explains the history of the Mts Al-Inthisor Bendega Tanjung Karang Sekarbela Educational Institution, Mataram City, West Nusa Tenggara. History is events or occurrences that occurred in the past that are studied and investigated to become a reference and guide for future life. Meanwhile, an educational institution is an institution or place where the education or teaching and learning process takes place. Madrasah Tsanawiyah Al Intishor was founded in 2000 with Government Decree Number wx/3-d/pp.03.2/1280/2001, dated 04 August 2001. MTs Al Intishor is one of the formal institutions under the auspices of the Al Intishor Islamic boarding school foundation led by TGH SUBA'I, Madarasah Tsanawiyah Al Intishor was built on a land area of ​​1400 m2. Madrasah Tsanawiyah Al Intishor Bendega Tanjung Karang Sekarbela, Mataram City, from its founding until now has experienced 6 changes in leadership (Madrasah Head). The development process of the Mts Al-Inthisor educational institution has increased over time in the development process, the school community as a whole, both teachers, teaching staff and students work together to realize the vision, mission and goals of the school.